Role of Interleukin-17 in immunopathology of chronic and aggressive periodontitis - Anand Narayanrao Wankhede; Prasad Vijayrao Dhadse (Wolters Kluwer Medknow Publications, 2019)
Interleukin-17 (IL-17) is a pro-inflammatory cytokine which is derived from T-cells. It is a strong agent of inflammation in inflammatory condition including the periodontitis. Several studies have focused on finding the role of IL-17 in the initiation and progression of chronic periodontitis and aggressive periodontitis (AgP). The aim of this review is to analyze the role of IL-17 in immunopathology of chronic periodontitis and AgP. An electronic literature search was conducted in the PubMed database using keywords aggressive, chronic, cytokine, IL-17, and periodontitis. A total of 152 publications were identified, wherein 43 studies fulfilled the inclusion criteria which were included and data extraction was done. Findings of these studies indicate that IL-17 is the important cytokine which plays a crucial role in the initiation and progression of periodontitis. More studies in all ethnic groups are necessary and hence that the predictive value (cutoff) of IL-17 levels in chronic and AgP can be determined.